Highspeed photography of gas release from bioactive glass - Postema, Michiel; Carlson, Craig; Anderton, N.; Xinyue, H.; Yamasaku, M.; Petit, L.; Massera, J.; Kudo, N. (IOP Publishing, 2024)
Bioactive glass has been of interest for applications in bone regeneration. Floating bioactive glass particles were observed to sink in ultrasound. The purpose of this study was to qualify and quantify bubble formation from floating bioactive glass particles. Water droplets containing borosilicate glass 13-93B20 particles, where 20% of the SiO2 was replaced with B2O3, of dimensions <38 μm were subjected to pulsed ultrasound, whilst being video-recorded at high speed. Measured radial expansions >20 μm corresponded to cavitation nuclei of initial radius 0.6 μm. This study provides experimental evidence that gas trapped inside bioactive glass may be released using high-amplitude ultrasound pulses.
Keywords: SDG-17: Partnerships for the goals